Comparative effectiveness of moderate hypofractionation with volumetric modulated arc therapy versus conventional 3D-radiotherapy after radical prostatectomy - Moll, Matthias; D'Andrea, David; Zaharie, Alexandru; Grubmüller, Bernhard; Paschen, Christopher; Zehetmayer, Sonja; Shariat, Shahrokh F; Widder, Joachim; Goldner, Gregor (Strahlentherapie und Onkologie, 2022)
PURPOSE: Hypofractionated radiotherapy for prostate cancer is well established for definitive treatment, but not well defined in the postoperative setting. The purpose of this analysis was to assess oncologic outcomes and toxicity in a large cohort of patients treated with conventionally fractionated three-dimensional (3D) conformal radiotherapy (CF) and hypofractionated volumetric modulated arc therapy (HF) after radical prostatectomy. METHODS: Between 1994 and 2019, a total of 855 patients with prostate carcinoma were treated by postoperative radiotherapy using CF (total dose 65-72 Gy, single fraction 1.8-2 Gy) in 572 patients and HF (total dose 62.5-63.75 Gy, single fraction 2.5-2.55 Gy) in 283 patients. The association of treatment modality with biochemical control, overall survival (OS), and gastrointestinal (GI) and genitourinary (GU) toxicity was assessed using logistic and Cox regression analysis. RESULTS: There was no difference between the two modalities regarding biochemical control rates (77% versus 81%, respectively, for HF and CF at 24 months and 58% and 64% at 60 months; p = 0.20). OS estimates after 5 years: 95% versus 93% (p = 0.72). Patients undergoing HF had less frequent grade 2 or higher acute GI or GU side effects (p = 0.03 and p = 0.005, respectively). There were no differences in late GI side effects between modalities (hazard ratio 0.99). Median follow-up was 23 months for HF and 72 months for CF (p < 0.001). CONCLUSION: For radiation therapy of resected prostate cancer, our analysis of this largest single-centre cohort (n = 283) treated with hypofractionation with advanced treatment techniques compared with conventional fractionation did not yield different outcomes in terms of biochemical control and toxicities. Prospective investigating of HF is merited.
Keywords: Prostatic Neoplasms; prostata; nádory prostaty; Humans; hypofrakcionace při ozařování; radioterapie s modulovanou intenzitou; bNED; lidé; Gastrointestinal toxicity; Radiation Dose Hypofractionation; Biochemical control; Prostatectomy; Postoperative; Male; Prostate; prostatektomie; Radiotherapy, Intensity-Modulated; mužské pohlaví; prospektivní studie; Genitourinary toxicity; Prospective Studies